Inventory Management Issues in Indian Steel Industry: A Qualitative Study (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2020)
Inventory management in Indian steel industry is felt as one of the unexplored area in terms of research practices. This study attempts to understand the major aspects of inventory management of Indian steel industry like major inventory management issues prevalent in steel firms, and impact of these issues, drivers, barriers, and possible measures that may help to resolve these issues. This study is based on an exploratory qualitative study of major Indian steel firms. The narratives reveal six major themes: Inventory management practices; Inventory issues in the steel industry; Major drivers for effective inventory management in Indian steel industry; Major barriers for the implementation of effective inventory management techniques including the implementation of ERP/MRP to manage inventories; Impact of inventory issues; Inventory control techniques to resolve these issues.